Efeitos da caprinocultura e desmatamento na composição e diversidade funcional de comunidades vegetais da Caatinga - Sousa, José Batista de (2020)
Goat farming is a widespread activity in most of the world's tropical dry forests. It mainly develops by converting forests into pasture areas which may negatively reflect the structure, composition and functioning of ecosystems. However, animal husbandry and deforestation can also be compatible with the diversity and functional composition of plant communities, and this understanding is still limited. Thus, these practices can contribute to the maintenance of processes such as biogeochemical cycles and ecosystem services, such as the provision of biomass. Although important, few studies measure the direct impact of goats on plant communities, especially in Brazilian semiarid regions, which have one of the highest human population densities in the world on drylands. Generally, in Caatinga, goat breeding is extensively developed, where the animals are basically supported by native pasture. Thus, our objective was to evaluate the effects of a goat grazing gradient and deforestation on the composition and functional diversity in plant communities. The study was conducted in fifteen (15) rural properties located in the cities of Pedro Avelino, Angicos and Lajes, located in the Central Mesoregion of Rio Grande do Norte. Interviews were conducted to obtain information about the properties as well as the characteristics of the herd that were used to calculate the animal load. Then, phytosociological and leaf surveys of plant communities were performed to mapping functional traits. For herbaceous plants, the traits height, leaf area and specific leaf area were measured, and for the tree / shrub, besides the traits mentioned above, we quantified the nitrogen, phosphorus and tannins of leaves. The functional composition of the areas was verified by the CWM, Community Weighted Mean of the traits and the functional diversity quantified by the Rao quadratic entropy index and compared to the Analysis of Covariance (ANCOVA) against time of deforestation and animal load. Herbaceous, shrub and trees together comprised 14.198 individuals belonging to 27 families and 85 species. Fabaceae and Poaceae families were the most abundant for tree and herbaceous, respectively. Significant results were found for functional diversity, specific leaf area and nitrogen contents (p <0.05) only for the woody stratum. There was greater functional diversity in areas with shorter land fallow (recent deforestation) and in areas with elevated animal pressure. Specific leaf area was positively correlated and nitrogen contents were negatively correlated with grazing intensity, showing lower concentrations under high grazing. However, it did not differ between types of deforestation. Thus, the present study suggests that goat farming affects the community since the animal load increased functional diversity as well as induced changes in the functional composition of the woody stratum. Moreover, no significant effects were found for herbaceous. Therefore, it is suggested that it is possible to maintain extensive animal husbandry without negatively impacting the functionality of the local herbaceous community, at least in the short term, given that this activity has a relevant importance for the northeastern semiarid farmers It is also considered necessary that other studies be carried out in the Caatinga to improve the knowledge about functional diversity in grazed areas associated with historical forms of use and occupation of this biome